Peningkatan Keahlian Podcast dalam Memanfaatkan Peluang ke Perguruan Tinggi pada Siswa Tingkat Akhir SMK Plus Muhajirin - Sutrisno, Sutrisno (Society : Jurnal Pengabdian Masyarakat, 2024)
SMK Plus Muhajirin, one of the leading private vocational high schools in Bandung City, West Java, Indonesia, offers a three-year educational program with a focus on Online Business and Marketing Skills Competencies. However, many students tend not to continue their education to tertiary institutions because of a lack of awareness of the importance of developing the skills acquired at vocational schools. To overcome this challenge, we organize knowledge development activities in the form of podcasts, aimed at equipping vocational school students with deeper knowledge in their areas of expertise. This podcast will be broadcast on YouTube channels and other social media, and will be published in accredited journals. It is hoped that this activity will provide vocational school students with additional insight and motivation to continue their education to higher education, while deepening the skills they have had since their vocational school days.